Based on biochemical and physiological behavior, where is Aspergillus egyptiacus better placed? - Zohri, A A; Ismail, M A (Folia microbiologica, 1994)
Physiological and biochemical properties were tested in 45 isolates of Aspergillus egyptiacus (16 isolates), Emericella nidulans (16) and Aspergillus versicolor (13). The three fungal species exhibited common and similar features. The big similarity between A. egyptiacus and E. nidulans was greater than between A. egyptiacus and A. versicolor. It included the inability to produce base either from sodium citrate or lactic acid media, growth at 45 degrees C (thermophilicity), and production of very similar pigmentations on Aspergillus flavus and parasiticus agar. A. egyptiacus is therefore better placed in the Aspergillus nidulans-Emericella assemblage.
Keywords: druhová specificita; Lactic Acid; Citric Acid; Culture Media; kyselina mléčná; Species Specificity; Urease; Citrates; ureasa; Aspergillus; katalasa; Aspergillus nidulans; sterigmatocystin; Sterigmatocystin; citráty; Amylases; amylasy; Lactates; laktáty; Catalase; Pigmentation; kyselina citronová; kultivační média; pigmentace